Shell Seekers - Colmar, Nicole (Auckland University of Technology, 2011)
Lost and found in translation: Being Madeleine This isn’t my life. This is the “screenplay” (book) I wrote about my life. Janet Frame (and me) Shell Seekers is a coming of age story of a young part ni-Vanuatu woman trying to reconcile her fragmented past. It is a past that is constructed through memory, fantasy and myth; from memories of an idyllic childhood in paradise, to the realities of educational aspirations in New Zealand, a return home permeated by local sweet/souring of Anglophile and Francophile colonial aftertastes, then as a young woman “in the belly of the beast” that is London, looking for a father and answers. A romantic encounter proves to be an eye-opener for Madeleine, who finally discovers that her displaced homeward journey is inevitably circular, and what “home” has become is borne out of memory, love and desire; a place she, literally, cannot “return” to again. Although many original works are often viewed as being semi-autobiographical, all the characters, including the central character of Madeleine Hughes are, in essence, fictions. Shell Seekers, the first ‘completed’ draft, is an original concept.
Keywords: Film; Cinema; Communications; Screenwriting; Narrative; South Pacific; Vanuatu; Coming of age